2016
DOI: 10.1177/0954405415619346
|View full text |Cite
|
Sign up to set email alerts
|

A generating milling method for a spur face gear using a five-axis computer numerical control milling machine

Abstract: To improve the machining accuracy and production efficiency of face gears, this article presents a generating milling method for the spur face gear using a five-axis computer numerical control milling machine and proposes a milling principle of the spur face gear using a milling cutter. Based on the milling principle and theory of gearing, a mathematical model of the spur face gear milling cutter is established, and the design parameters of the cutter are determined. Considering the requirements of machine mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Considering equations (7) and (14) simultaneously, the meshing equation of the generated spiroid gear and the virtual hob cutter is determined as…”
Section: Geometry Of the Imaginary Generating Fully Conjugated Spiroimentioning
confidence: 99%
See 1 more Smart Citation
“…Considering equations (7) and (14) simultaneously, the meshing equation of the generated spiroid gear and the virtual hob cutter is determined as…”
Section: Geometry Of the Imaginary Generating Fully Conjugated Spiroimentioning
confidence: 99%
“…Parameters R 2 and R 1 determine the outer and inner dimensions, respectively, of the spiroid gear and can be obtained from the conditions of avoidance of undercutting and pointing. 14 Angle γ m is formed by the axes of the gear and the hob. In this article, the angle γ m between the two axes is limited to 90°.…”
Section: Generation Of the Spiroid Gearmentioning
confidence: 99%
“…Khaghani and Cheng 18 presented an approach to tool path generation for ultraprecision machining of freeform optic surfaces. Wang et al 19 proposed a milling method for a spur face gear using a five-axis NC milling machine. This study demonstrated that the generating milling method could be applied in precision milling of the spur face gear.…”
Section: Introductionmentioning
confidence: 99%
“…Litvin and Fuentes 3 and Dudley 4 made a detailed analysis of the gear meshing principle, gear machining and tooth contact in their textbook. Based on the principle of milling and the theory of gear meshing, Wang et al 5 put forward a high-efficiency and high precision machining method of spur face gear. Han et al 6 and Tian et al 7 proposed an embedded reconfigurable EGB platform which contains parametric programming and process database module and verified the correctness and effectiveness of the platform on a six-axis gear hobbing machine.…”
Section: Introductionmentioning
confidence: 99%